Social movements and social networks: The participation of young people in Peru - La Rosa Pinedo, Amaro Elías (2022)
Social movements throughout history have been catalysts of great social changes. In some cases, their achievements were notable, achieving changes in public policies, expanding social rights, as well as the defense of various social sectors. In other cases, the result of the mobilization was less tangible. In the present article a review of the transcendence and evolution of the so- cial movements of the past is carried out, focusing especially on those that implied the active participation of young people. In the same way, the current social mobilization involving the use of social media is presented. Networ- king is a virtual meeting point between citizens who seek to express their disagreements. In the final part, the study focuses on the case of the move- ment against the so-called Pulpín Law in Peru. Social networks are consider as important as the variables of the context in which the protest is generated.